Analisa Model Bisnis Bank Umum Syariah di Indonesia - Angga Darmawan (JESI (Jurnal Ekonomi Syariah Indonesia), 2020)
This research purpose is to find an alternative business model that can be implemented by Islamic bank in Indonesia, hence the Islamic bank can optimally growth. This research conducts several stages of research. Indepth interviews were conducted to get an idea of the need for a new Islamic Bank business model. The results of the interview are used as the basis for designing the business model of the Islamic Bank using the Analytic Network Process (ANP) method framework and the questionnaire model to obtain the required data. Based on the interview results, there are 4 (four) alternative islamic banking business models, namely Islamic Commercial Bank, Islamic Commercial Bank with Backed Asset, Integration of Islamic Commercial Bank and Islamic Social Bank, and Waqf Bank. The results of this study indicate that the Wakaf Bank Business Model (25.42%) is the main priority of the respondents in the islamic commercial bank business model.